Implant comparisons in feedlot steers and heifers - T.P. Eck; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1993)
Feedlot performance of steers implanted with Compudose®, Implus-S®, or Synovex-S® was very similar. No statistical differences were detected among treatments. However, implanted steers gained an average of 4% faster than nonimplanted controls. Carcass quality was virtually unaffected by treatment. Implanting feedlot heifers with Synovex- H®, Implus-H®, or Implus-H® plus Finaplix- H® increased daily gain compared to non-implanted heifers. Implanting improved gain and feed efficiency by 13 and 7.1%, respectively, compared to controls. Differences in carcass characteristics probably were due to the increased weight gain associated with implants. Percentage of carcasses grading Choice was not impacted by treatment.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Feedlot; Steer; Heifer; Implants